Improvement of sperm morphology after surgical varicocele repair. (6th May 2021) - Morini, Daria; Spaggiari, Giorgia; Daolio, Jessica; Melli, Beatrice; Nicoli, Alessia; De Feo, Gaetano; Valli, Barbara; Viola, Domenico; Garganigo, Simona; Magnani, Elena; Pilia, Annalisa; Polese, Alessandra; et al.
Abstract: Background: A causative relationship between varicocele and impairment of semen quality has been largely investigated in the context of male infertility, although its clinical benefit remains controversial. Objective: To investigate the effect of varicocele correction on detailed morphologic microscopic semen parameters in a large homogeneous cohort of patients and to evaluate which factors could predict semen improvement after the surgical treatment. Materials and methods: An observational, retrospective cohort study was carried out including all patients undergoing surgical treatment for varicocele from September 2011 to March 2020 in the same clinical centre. Enrolled males performed at least one semen analysis before and one after surgical varicocele correction. Primary outcome was the detailed morphologic microscopic sperm evaluation. Secondary outcomes were conventional semen analyses. Results: A total of 121 males (mean age 24.6 ± 6.1 years) were enrolled. Using detailed morphologic microscopic sperm evaluation, a significant morphological improvement was recorded, with a reduction in head and tail abnormalities. Moreover, a significant increase in sperm concentration ( p = 0.015) and percentage of progressive and total motility ( p = 0.022 and p = 0.039) were observed after surgery. The multivariate logistic analysis identified the ultrasonography varicocele degree before surgery as a main predictor of the sperm concentration improvement ( p = 0.016), with the highest improvement for varicocele of I and II degree. Discussion: For the first time, the detailed morphologic microscopic sperm evaluation highlights a relevant reduction in sperm abnormalities after varicocele surgery, showing its potential application in clinical practice.